The Role of Religious Leaders in Building Inter-Religious Harmony in Multicultural Society - Tri Miratul Hasanah; Jaenullah Jaenullah; M. Agus Mushodiq (Assyfa Journal of Islamic Studies, 2025)
This research is motivated by the multicultural condition of Indonesian society with the potential for interreligious conflict, yet on the other hand there is a strong phenomenon of harmony in Bumi Raharjo Village, Bumi Ratu Nuban District, Central Lampung Regency. This study aims to analyze the condition of interreligious harmony and the role of religious leaders in building such harmony based on Anthony Giddens' structuration theory. The research uses a qualitative approach with field research type. Data collection techniques include observation, in-depth interviews, and documentation. Research informants include Islamic and Hindu religious leaders, village officials, and community members from various religious backgrounds. Data analysis was conducted through data reduction, data display, and conclusion drawing with validity testing using source and technique triangulation. The results show that interreligious harmony in Bumi Raharjo Village is manifested in the form of tolerance (mutual respect for worship), effective communication, and social cooperation (mutual cooperation, village activities, and cross-religious involvement of Karang Taruna). The role of religious leaders in structuration theory includes three dimensions: (1) signification, namely the formation of inclusive religious meaning through sermons and advice about tolerance; (2) domination, namely directing community social actions through role modeling and involvement in social activities; (3) legitimation, namely providing normative justification for harmonious practices as part of religious teachings. Supporting factors for harmony include high community awareness, harmonious social relations, village government support, and the active role of religious leaders. Inhibiting factors include differences in religious understanding, lack of tolerance education, and external influences such as hoaxes and interfaith families. This study concludes that religious leaders act as strategic structuration agents in creating and maintaining harmony in multicultural societies.